Papiliotrema flavescens, a plant growth-promoting fungus, alters root system architecture and induces systemic resistance through its volatile organic compounds in Arabidopsis - Liu, Siyue (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2024 Elsevier Masson SAS. All rights reserved.